FACTORS AFFECTING THE FINANCING OF THE MSME SECTOR IN SHARIA BANKING IN INDONESIA: AUTOREGRESSIVE DISTRIBUTED LAG (ARDL) APPROACH - Anggreyni, Reza Dwi; Shofawati, Atina (Jurnal Ekonomi Syariah Teori dan Terapan, 2020)
This study aims to determine the effect of inflation, BI Rate, exchange rate, Industrial Production Index (IPI), Third Party Funds (DPK), on MSME sector financing in Islamic banking in Indonesia, both short term and long term periods from January 2014 until December 2018. This research uses a quantitative approach with Autoregressive Distributed Lag (ARDL) analysis technique. The result showed that inflation had a significant negative effect on the short and long term on MSME sector financing, while BI Rate and DPK had a significant positive effect on MSME financing in the short and long term. The exchange rate has a significant negative effect on MSME financing in the short and long term, while IPI has no significant effect on MSME financing in the short and long term in Islamic banking in Indonesia Keywords: Financing, MSME, Islamic Banks, ARDL REFFERENCES Azis, S. A. (2009). Al-Zakah. Terj. Ummu Abdillah al-Buthoniyah. Retrieved November 24, 2018, from http://www.raudhatulmuhibbin.org Badan Pusat Statistik. (2017). Gini Rasio 2016 Kota Yogyakarta. Yogyakarta: Badan Pusat Statistik. Badan Pusat Statistik. (2018). Keadaan Ketenagakerjaan Indonesia. Jakarta: Badan Pusat Statistik. Bank Indonesia. (2016). Metadata. Jakarta: Bank Indonesia. Bappenas. (2012). Rasio Gini di Indonesia dalam Lima Tahun Terakhir. Retrieved from Bappenas Web site: https://www.bappenas.go.id Bappenas. (2016). Siaran Pers: Mencapai Pertumbuhan Ekonomi 5,3% serta Pengurangan TPT 5,3-5,6% pada 2017. Jakarta: Bappenas. Beik, I. S., & Aprianti, W. N. (2013). Analisis Faktor-Faktor yang Memengaruhi Pembiayaan Bank Syaria untuk Sektor Pertanian di Indonesia. Jurnal Agro Ekonomi. Hadliroh, M. (2014). Factors Influencing Poverty in East Java Province, Indonesia Year 2000-2013. Journal of Economics and Sustainable Development. Harris, R. I. (1995). Cointegration Analysis in Econometric Modelling. Great Britain: Prentice Hall. Indonesia Investments. (2018). Inflasi di Indonesia (Indeks Harga Konsumen). Retrieved from Indonesia Investments: www.indonesia-investments.com Jusmaliani, & Soekarni. (2005). Kebijakan Ekonomi dalam Islam. Yogyakarta: Kreasi Wacana. Mankiw, N. G. (2000). Teori Makro Ekonomi Edisi Keempat, ter. Imam Nurmawan. Jakarta: Penerbit Erlangga. Mawardi, I., & Widiastuti, T. (2015). Kesejahteraan dan Kemiskinan dalam Perspektif Islam. Surabaya: STAINA PRESS. Putra, L. D. (2011). Analisis Pengaruh Ketimpangan Distribusi Pendapatan terhadap Jumlah Penduduk Miskin di Provinsi Jawa Tengah Periode 2000-2007. Semarang: Universitas Diponegoro. Ravallion, M. (2001). Growth, Inequality, and Povery: Looking Beyond Averages. World Development Vol. 29 No. 11. Rosadi, D. (2011). Analisis Ekonometrika dan Runtut Waktu Terapan dengan E-Views. Yogyakarta: ANDI. Talukdar, S. R. (2012). The Effect of Inflation on Poverty in Developing Countries: A Panel Data Analysis. Texas: Texas Tech University. UN. (2010). Rethinking Poverty: Report on the World Social Situation. Department of Economic.